1991
DOI: 10.1246/bcsj.64.1071
|View full text |Cite
|
Sign up to set email alerts
|

The Photosensitized Oxygenation of Furanoeremophilanes. III. The Transformations to the Skeletally Isomeric Lactones from Furanofukinol

Abstract: Pairs of the skeletal isomers of eremophilane-type lactones were synthesized from furanofukinol via photosensitized oxygenation, followed by lactone cleavage and reformation. Their stereochemistry has been clarified so as to be consistent with a classification method outlined in our earlier papers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Lactones, which only differed in the configuration at C 8 , exhibited CD spectra with opposite directions (nonsteroid-like 8a-stereoisomer 2; steroid-like 8b-stereoisomer 1). [43][44][45][46] In agreement with these observations, the CD spectra of 7 and 8 had negative signs with minima at k 5 224.0 nm (De 5 29, 7) and k 5 223.8 nm (De 5 29, 8), respectively. Both CD spectra were almost superimposable, indicating that the influence of the ester side chain on the CD may be negligible (Fig.…”
Section: Experimental CD Spectroscopy Of Compounds 2 To 10supporting
confidence: 79%
“…Lactones, which only differed in the configuration at C 8 , exhibited CD spectra with opposite directions (nonsteroid-like 8a-stereoisomer 2; steroid-like 8b-stereoisomer 1). [43][44][45][46] In agreement with these observations, the CD spectra of 7 and 8 had negative signs with minima at k 5 224.0 nm (De 5 29, 7) and k 5 223.8 nm (De 5 29, 8), respectively. Both CD spectra were almost superimposable, indicating that the influence of the ester side chain on the CD may be negligible (Fig.…”
Section: Experimental CD Spectroscopy Of Compounds 2 To 10supporting
confidence: 79%
“…Then the chemical shift of H-23 was downfield from that of H-24, suggesting that 4 possessed a cis -eremophilanyl unit and a β-oriented OH-19. Based on the Naya rules, the homoallylic coupling between H-13α and H-22 observed in the 1 H– 1 H COSY spectrum indicated that OH-21 was β-configurated. Furthermore, the key NOESY correlation of H-20α/H-1 demonstrated the α-orientation of C 3 -carbonyl group.…”
Section: Resultsmentioning
confidence: 79%
“…Furthermore, the absolute stereochemistry of 1 was elucidated by applying the empirical rule for the α,β-unsaturated γ-lactone of eremophilane-type sesquiterpenoids in circular dichroism (CD) spectrum. The negative Cotton effects, observed at 245 nm, substantiated the absolute configuration of C-8 to be R. 8,10) Culcitiolides F and G (2, 3) were purified as an inseparable mixture of two structural isomers. The molecular formulas of these isomers were established by HR-FAB-MS as C 21 4,5,7,11) with the ratio of 1 to 1.…”
Section: Resultsmentioning
confidence: 89%
“…3). The NOE enhancements for H-14/H-3 β , H-14/H-6, H-14/H-10, H-15/H-3 β and H-4/H-6 indicated that these compounds contain a cis-decalin ring system with a steroidal-like conformation 7,10) and that each acyl group was in the β-orientation. Furthermore, the direction of methoxy group (C-16) was determined to be β-orientation according to the above mentioned rules reported by Naya et al [8][9][10] Based on these results, the relative stereochemistries of culcitiolides F and G were determined as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%